Effect of fingolimod (FTY720) on cerebral blood flow, platelet function and macular thickness in healthy volunteers. (December 2014) - Ocwieja, Magdalena; Meiser, Karin; David, Olivier J.; Valencia, Jessica; Wagner, Frank; Schreiber, Stephan J.; Pleyer, Uwe; Ziemer, Sabine; Schmouder, Robert
<x xml:space="preserve">Abstract</x> Aim Fingolimod, a sphingosine 1‐phosphate receptor modulator, is the first oral disease modifying therapy approved for the treatment of relapsing multiple sclerosis. The aim of this double‐blind, placebo‐controlled study was to evaluate the effect of fingolimod on cerebral blood flow, platelet function and macular thickness in healthy volunteers. Methods The study included 88 healthy volunteers who received fingolimod 0.5 mg or 1.25 mg or matched placebo over a period of 4 weeks. Transcranial colour coded sonography was performed to measure mean blood flow velocities, the platelet function was measured by the PFA‐100® assay using a collagen/epinephrine cartridge and macular thickness was measured using optical coherence tomography. An assessment of non‐inferiority of fingolimod vs. placebo was performed against a reference value (20% of the overall baseline value). Results All 88 randomized participants completed the study. At day 28 compared with baseline value, for 0.5 mg, 1.25 mg and placebo treatments, the mean middle cerebral artery blood flow velocity decreased by 4, 1 and 3.7 cm s−1, respectively. The platelet function analyzer closure time increase was not significant (7.8, 7.5 and 10.4 s, respectively). The mean percentage change in the central foveal thickness from baseline for both eyes was below 3% for all groups. The safety profile of fingolimod in this study was found consistent with the previous reports. Conclusions In healthy volunteers, the changes seen with both fingolimod doses were found to be within normal variability, non‐inferior and comparable with those observed with placebo for all the pharmacodynamic parameters assessed.